The Future is Traceable: Integrating Blockchain, Waste Management, and the Circular Economy for Sustainability - Rahman, M Abeedur; Chowdhury, Kaushik; Chowdhury, Lutfun Nahar; Mallik, Shuvo Kumar; Nova, Noushin Akhter (Journal of Posthumanism, 2025)
Blockchain technology's emergence in waste management (WM) offers a fresh approach to addressing problems, including efficiency, transparency, and traceability. However, the lack of transparency in tracking trash from its production to its disposal makes traditional waste management frameworks vulnerable to fraud, poor management, and inefficiency. Blockchain provides a safe and immutable platform that records every stage of the waste lifecycle, enabling real-time verification and monitoring. This study sheds light on how blockchain technology, in conjunction with smart contracts, might improve recycling and promote waste operations' transparency. The idea of a digital product passport is also reinterpreted in the larger framework of trash recycling and the circular economy (CE). The study demonstrates the need to develop indicators for SWM efficacy assessment using data from Scopus and WoS (Web of Science) and R and Bibliometrics tools.